Labor Skills and International Trade: Evaluating Many Trade Flows with a Single Measuring Device - Keesing, Donald B. (The Review of Economics and Statistics, 1965)
PURSUING the methods by which Leontief discovered his renowned paradox, previous empirical studies of the relationship among factors, production, and trade have computed the content of a single country's trade from the factor requirements of its production processes.' The present study introduces a somewhat different method. The assumption is made that all manufactured goods traded, not only by the United States but by other countries as well, are produced with a single set of technical coefficients, namely the combinations of labor skills observed in each industry in the United States. It is postulated that the availability of labor skills determines patterns of international location and trade for a broad group of manufactured products, those not closely tied to natural resources. It is further supposed that the relationship between trade and skills for these goods will reveal itself in American skill requirements for reproducing trade flows. The first expectation seems plausible. Direct capital requirements are not as high in manufacturing as in most other activities.2 Labor appears to be less mobile internationally than liquid capital or capital goods. Generations of industrial experience and education may be required to build a skilled labor force. Let me spell out the basic method before examining its rationale. As in Leontief's computations, production functions are assumed to involve simple linear combinations of factors. There are no scale effects, and factors are perfectly divisible. We define Si as a quantity of the ith factor, such as labor of a specified skill class; Xj is the quantity of the jth product traded, so that XI, X2, X3, . . . , Xm describes the composition of a trade flow such as Japanese exports.3 To determine the skills required to produce this trade flow with American coefficients, we multiply our m-item trade vector X by an m X n matrix A, in which the elements aij (i= 1, 2, . . . n; j=1, 2,... m) represent average United States direct requirements for labor of n skill classes to produce a unit of output of each product. The result, the vector SI, S2, S3, . . . , SX, shows United States skill requirements for producing the goods in the trade flow.